Rintangan Komunikasi Antarbudaya Antara Sikap dan Persepsi Masyarakat Makassar terhadap Mahasiswa Etnis Papua di Kota Makassar - Blasius Yolfarin Becang; Erniwati Erniwati; Nurdyansa Nurdyansa (Dialogika : Jurnal Penelitian Komunikasi dan Sosialisasi, 2025)
This research is motivated by the miscommunication that has recently occurred in the city of Makassar between Makassar community members and Papuan students, so it is interesting to study from the perspective of intercultural communication with the aim of knowing the intercultural communication process that occurs and the factors that influence the intercultural communication process between the Makassar community and Papuan students in the city of Makassar. The method used in this study is a qualitative descriptive method and the researcher used a purposive sampling technique to select subjects with 4 Papuan students and 7 Makassar community members so that the total number of informants was 11. The data sources used were primary and secondary data sources related to the empirical situation or condition with interviews and documentation in order to obtain primary data regarding the purpose of the study. The results of this study indicate that the intercultural communication process carried out by the Makassar community and Papuan students occurred quite smoothly with an attitude of mutual cooperation, tolerance and being quite friendly to each other and living side by side. The obstacles to intercultural communication, both Papuan students and Makassar community still have difficulty in understanding each cultural difference. Other obstacles in intercultural communication are differences in language, dialect and their perceptions in assessing each culture.